Granulomatous dermatitis post Mycobacterium Indicus Pranii (MIP) vaccine in severe covid-19 infection: an exaggerated hypersensitivity phenomenon - Pooja Agarwal; Raju Chaudhary; Kalgi Baxi; Malhar Shah (Journal of the Egyptian Women’s Dermatologic Society)
Mycobacterium indicus pranii (MIP) vaccine is widely used in dermatology as immunotherapy for warts as well as in patients with leprosy. During the COVID-19 pandemic, a positive role of MIP as an immunomodulator in SARS-CoV-2 disease was reported after pilot research, with minor adverse effects. We report a case of a 65-year-old male, presenting with skin lesions suggestive of noninfective granulomatous dermatitis for 4 months, at the sites of MIP intradermal injections, allegedly received during a hospital stay for severe COVID-19 disease. The patient presented with nonhealing nodulo-ulcerative lesions at the sites of injection, which persisted for 4 months associated with intermittent serous discharge and showed no signs of healing despite supportive treatment. The patient was started on a combination therapy of ofloxacin 400 mg /day and clarithromycin 500 mg 12 hourly for 2 months. At the end of 2 months, all the lesions showed complete healing with a resolution of discharge and nodularity, leaving behind postinflammatory hypopigmentation and atrophic scarring. The patient was followed up for 4 months after stopping treatment during which time he had no relapse of the lesions. This case has been reported to the India Pharmacopoeia.